INFLUENCE OF SEED QUALITY AND SOIL FERTILITY MANAGEMENT ON THE PRODUCTIVITY OF RICE (ORYZA SATIVA L.) IN THE GUINEA SAVANNA OF GHANA - Dogbe, W.; Dzomeku, I. K.; Yahaya, B. S.; Siise, A.; Krofa, E. O.; Awuakye, S. A. (UDS International Journal of Development, 2016)
Seed quality and soil fertility improvement are two key determinants of enhanced crop production to ensure food security in the savannah ecology. Field studies were conducted at the experimental field of the Savanna Agricultural Research Institute (SARI) during the 2011 and 2012 cropping seasons, from July to November, to determine the interaction effects of seed quality and soil amendments on yield components and grain yield of Gbewaa rice (Jasmine 85). Seed quality, using farmer-saved seed and certified seed, was combined with five levels of soil amendments and laid out in a randomized complete block design with four replications. The soil amendments were: No-amendment control, 28.75-12.5-6.25 kg NPK/ha and 60 kg urea /ha (55.2 kg N/ha) as basal and top-dressing applications, respectively (Half Recommended Rate of inorganic fertilizer = HRR), Half Recommended Rate of inorganic fertilizer + 1.5 tonnes of compost per hectare, 57.5-25-12.5 kg NPK/ha and 120 kg urea/ha (110.4 kg N/ha) as basal and top-dressing applications, respectively (Recommended Rate of inorganic fertilizer = RR) and Recommended Rate of inorganic fertilizer + 3 tonnes of compost/hectare. In 2011, improved seed quality in combination with soil amendments made significant improvements in panicle length (P<0.03), number of seeds per panicle (P<0.01) and thousand-grain weight (P<0.04). Parameters that improved in both years with improved seed quality and also soil amendments were tiller count (P<0.01), number of seeds per panicle (P<0.01), and grain yield (P<0.001), with certified seed gave better results than farmer-saved seed, whilst RR + 3 t/ha compost optimized each parameter. However, RR alone promoted grain yield similar to RR + 3 t/ha compost. Tiller count (r=0.889**), number of panicles per hill (r=0.834**), number of seeds per panicle (r=0.922**) and thousand grain weight (r=0.893**) were all positively correlated with grain yield in 2012. Tiller count consistently accounted for more than 75% of the grain yield. The food security implications of the results are discussed in the full paper. Keywords: Soil Management, Rice production, Seed Quality, Guinea Savanna